PENDIDIKAN ANAK DALAM PERSPEKTIF ISLAM PADA ARTIKEL-ARTIKEL KELUARGA HEBAT DI LAMAN SAHABAT KELUARGA - Kurniawan, Heru; Istiani, Diah; Ngilmiyah, Rofikoh (Universitas Negeri Jakarta, 2021)
The Rubric of Keluarga Hebat on page Sahabat Keluarga discusses successful parental education practices in children. One of the educational practice is education based on Islamic value and teaching. Through these Islamic education practices, the concept of education can be found which refer to the first, the concept of exemplary education that puts forward good example of parents in educating children. Second, the concept of disciplinary education which emphasizes the importance of enforcing discipline for children, both discipline of time, duty and responsibilities, and commitment. Third, the concept of habituation education, which is an intense attitude in getting used to good deeds in children so that children will get used to doing good. Fourth, the concept of prayer education, which builds awareness in children that one of the important role in life is prayer. Sixth, the concept of repetition that teaches the importance of repetition of good education principle continously so that it internalizes in the children. Sixth the concept of communication education, which is the importance of building communication between parents and children. These five concepts are derived from Islamic teaching and value that have been successfully practiced by parents so that their children can be successful.